Efficacy of EMG Biofeedback Cervical Traction on Patients with Unilateral Cervical Radiculopathy - Semary, Moataz M. El; Elzanaty, Mahmoud Y.; Galal, Dina O.; El-Serougy, Hager R.; Abdelmageed, Shaima M.; Taha, Shreen I. (International Journal of Psychosocial Rehabilitation, 2020)
Background: Cervical radiculopathy (CR) is frequently encountered by physical therapists, so EMG effects biofeedback cervical traction on myoelectric activity of Paraspinal cervical muscles that can give better effect on neck pain and cervical ranges of movements. Objective: This study aimed to assess efficacy of cervical traction maneuver with and without EMG biofeedback for neck muscle where C5 CR. Subjects and methods: thirty male have CR secondary to C5- C6 cervical disc herniation, picked by convenience sampling and Fifteen allocated randomly to cervical traction maneuver with EMG biofeedback (Group A); and fifteen patients to conventional traction (Group B). Exercised for intermittently for 20 min. with 10 seconds pull and 5 seconds rest cycle. Angle of pull adjusted at 25˚ from vertical plane, at 2 /week for 45 days. and the traction force was adjusted at one fourth of body weight during pull and one eighth during rest. Results: reducing of myoelectric activities were identified throughout traction pull phase and later in cervical muscle tension, during the six-weeks course especially in people use EMG biofeedback traction modality and also in VAS & cervical movements. Conclusion: EMG biofeedback in comparison with cervical traction training can lessen muscle tension effectively resulting in more pain inhibition and grants more range of cervical movements.